PENERAPAN LITERASI SAINS MELALUI PEMANFAATAN ECOBRICK DI KELAS V SD NEGERI 1 TANRUTEDONG KABUPATEN SIDENRENG RAPPANG - Bachri, Rini Aden Kartika; St. Muriati; Nasiruddin, Fathimah Az Zahra (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
Scientific literacy is not just reading but students are able to think at a high level and evaluate directly so that learning will be remembered longer by students, besides those environmental problems are of great concern globally today, namely plastic waste, by introducing ecobrick to students, the waste will be delayed until the sea but can be utilized. Ecobricks are solid plastic bottles filled with non-biological waste to make reusable building blocks. This research was conducted with the aim of knowing the application of scientific literacy through ecobricks at fifth grade students of SD Negeri 1 Tanrutedong, Sidenreng Rappang Regency. This type of research is qualitative, namely through interviews, observation and documentation. The results obtained from the implementation of scientific literacy through ecobricks at class V are on each scientific literacy indicator, namely: 1) The contact stage opens learning activities by discussing the waste that is around students, 2) The curriculum stage, attracts students' attention to focus on the material but with a relaxed atmosphere, 3) The concept formation stage makes students active in learning with discussion sessions, 4) The decision-making stage, takes a logical decision on the problem, is enthusiastic about assembling ecobricks before they have not known and studied ecobricks as plastic waste recycling, 5) Concept development stage students can mention the essence of learning, namely how to distinguish types of waste, keep the environment clean, and recycle plastic waste through ecobricks, 6) Evaluation stage students are able to complete the manufacture of ecobricks, 330 ml bottles with an ecobrick weight of 110 grams. So, the implementation of scientific literacy ecobricks at class V of SD Negeri 1 Tanrutedong, Sidenreng Rappang Regency in every scientific literacy indicator has been carried out well. Supporting factors that influence the implementation of scientific literacy, due to the interesting and unique learning process because previously students have never studied ecobricks combined with scientific literacy, students also have curiosity so that researchers maximize to stimulate students and the learning process was centered on students, and this research was carried out in an open field so that students felt comfortable and the subject matter raised was very contextual. Learning scientific literacy can be integrated into other subjects by linking it to ecobricks.